Polyethylene resin composition for highly lubricative film and highly lubricative film laminate

JP2025024646APending Publication Date: 2025-02-20JAPAN POLYETHYLENE CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023128911
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-07
Publication Date
2025-02-20

AI Technical Summary

Benefits of technology

【0014】 本発明の高滑性フィルムは、樹脂層同士の滑り性に優れ、包装用成形品としてヒートシール性などの本来の要求特性を損なうことがない。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025024646000001_ABST
    Figure 2025024646000001_ABST
Patent Text Reader

Abstract

To provide a polyethylene resin composition for lamination and a highly lubricative laminate which exhibits excellent lubricity without impairing quality such as heat seal.SOLUTION: A highly lubricative film laminate includes one or more resin layers (A) which have a coefficient of static friction of a gradient method therebetween of less than 0.5, and which satisfy the following characteristics: the resin layer (A) includes a resin composition containing an ethylene-propylene copolymer having (c-1) to (c-5), and high pressure radical polymerization method low density polyethylene having (d-1) to (d0-2). Therein (c-1) an ethylene-derived unit is 75-93 mol%, and a propylene-derived unit is 7 to 25 mol%, (c-2) an MFR is 1 to 100 g / 10 min, (c-3) density is 0.87 to 0.91 g / cm3, (c-4) a total content of vinyl and vinylidene in a copolymer is 0.20 (piece / total 1,000C) or more, (c-5) a number (Y) of branches in a copolymer and density (X) have a relation satisfying Expression: (Y)≥-1,360×(X)+1,270, (d-1) an MFR is 0.1 to 20 g / min, and (d-2) density is 0.915 to 0.930 g / cm3.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyethylene resin composition for high lubricity films and a high lubricity film, and more particularly to a polyethylene resin composition used by laminating it to a substrate such as paper or film, and a high lubricity film made therefrom, which has high lubricity and excellent heat sealability. The present invention relates to a polyethylene resin composition for high lubricity films and a high lubricity film laminate. [Background technology]

[0002] Conventionally, thin-walled resin molded articles (films, containers, etc.) have been widely used to package various components, foods, and other products. When packaging various components, foods, and the like, the above-mentioned packaging molded articles may require lubricity, particularly on the inner surface. The following techniques are known for imparting lubricity to the inner surface of the packaging molded articles.

[0003] For example, Patent Document 1 discloses a method of adding a fatty acid ester lubricant such as stearate monoglyceride to impart lubricity to the inner surface of a packaging molded article. Patent Document 2 discloses a method of adding a lubricant made of an anionic surfactant having at least one selected from a group represented by -(AO)n- (A is an alkylene group having 2 to 4 carbon atoms, n is a number such that the AO fraction in the molecule is 10 to 80%, and n As may be the same or different) or an aromatic ring, and an anionic group in the molecule.

[0004] However, the method of expressing slipperiness by adding lubricants which are low molecular weight compounds is not preferred because it is difficult to control bleeding due to temperature or time, and also because it is prone to problems such as poor sealing between the inner surfaces of the molded packaging article in areas where a large amount of lubricant has bled out.

[0005] In view of this, as a method for imparting slipperiness without incorporating a lubricant, for example, Patent Document 3 proposes a method in which a film is brought into contact with a roughened heated roll to transfer unevenness to the film surface. However, this requires a reheating roll with a specific surface shape, which not only makes it unavoidable to incur investment costs, but also makes it difficult to say that the effect of imparting slipperiness is sufficient, limiting the uses of the film to which it can be applied. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 11-343353 [Patent Document 2] JP 2003-313432 A [Patent Document 3] JP 2012-57147 A Summary of the Invention [Problem to be solved by the invention]

[0007] In view of the above problems, an object of the present invention is to provide a polyethylene resin composition for a high-slippery film and a high-slippery film laminate which impart good slip properties without adding a lubricant which is a low molecular weight compound, and which does not impair other qualities of a molded packaging article other than the slip properties. [Means for solving the problem]

[0008] As a result of intensive investigations aimed at solving the above problems, the present inventors have newly produced ethylene-propylene copolymers having new physical properties in the new ranges of (c-1) to (c-5) shown below, and have found that a laminate having such specific properties, i.e., an ethylene-propylene copolymer which contains a specified amount of a main component which is ethylene and a sub component which is propylene, has a density and MFR within a certain range, has a large amount of double bonds contained in the copolymer, and has a large number of branches, and further contains a specific high-pressure radical polymerization low-density polyethylene, has excellent slip properties and does not impair other qualities such as heat seal strength, thereby completing the present invention.

[0009] That is, according to the first aspect of the present invention, there is provided a highly lubricating film laminate having at least two layers, namely a resin layer (A) and a base layer (B), wherein the resin layer (A) is formed directly on the base layer (B) or by laminating it on another resin layer laminated on the base layer, and wherein, when the resin layers (A) of the obtained laminate are superimposed on each other, the static friction coefficient measured by the inclination method under conditions of 23°C-50RH in accordance with JIS P8147 is less than 0.5, and further, the resin layer (A) and the polyethylene resin composition (E) constituting the resin layer (A) satisfy the following properties: Resin layer (A): A polyethylene resin composition (E) containing an ethylene-propylene copolymer (C) having the following characteristics (c-1) to (c-5). (c-1) Contains 75 to 93 mol% of structural units derived from ethylene as a major component, 7 to 25 mol% of structural units derived from propylene as an essential minor component, and may contain up to 7 mol% of structural units derived from a third α-olefin other than ethylene and propylene as a minor component. (However, when the structural units derived from the third α-olefin are contained, the total content of the structural units derived from ethylene, the structural units derived from propylene, and the structural units derived from the third α-olefin does not exceed 100 mol %). (c-2) MFR (190℃, 21.18N load) is 1-100g / 10min (c-3) Density is 0.87 to 0.91 g / cm 3 (c-4) The total amount of vinyl and vinylidene in ethylene-propylene copolymer is 0.20 (pieces / total 1000C) or more (Note that the number of vinyl and vinylidene units is the number per 1,000 carbon atoms in the main chain and side chains, measured by NMR.) (c-5) The number of comonomer branches (Y) and density (X) in the ethylene-propylene copolymer satisfy the relationship shown in formula (1) below. Formula (1): (Y) ≧ -1360 × (X) + 1270 (where Y is the number per 1000 carbon atoms in total in the main chain and side chains as measured by NMR.) Polyethylene resin composition (E): A polyethylene resin composition (D) containing a low-density polyethylene (D) produced by a high-pressure radical polymerization method and having the following characteristics (d-1) to (d-2). (d-1) MFR (190℃, 21.18N load) is 0.1 to 20g / 10min (d-2) Density is 0.915 to 0.930 g / cm 3

[0010] In addition, according to a second aspect of the present invention, there is provided a highly lubricating film laminate according to the first aspect, characterized in that the polyethylene resin composition (E) further satisfies the following properties (e-1) to (e-2): (e-1) MFR is 1 to 100 g / 10 min (e-2) Density is 0.88 to 0.94 g / cm 3

[0011] In addition, according to a third aspect of the present invention, there is provided a highly lubricating film laminate according to either the first or second aspect of the present invention, characterized in that the laminate is formed by an extrusion coating method.

[0012] According to a fourth aspect of the present invention, there is provided the high lubricating film laminate according to the first or second aspect, characterized in that the resin layer (A) is an outermost layer or an innermost layer of the laminate.

[0013] In addition, according to a fifth aspect of the present invention, there is provided a polyethylene resin composition for a high lubricating film, which is contained in a resin layer (A) used as an outermost layer or an innermost layer of a high lubricating film laminate, and which has a static friction coefficient of less than 0.5 by an inclination method measured under conditions of 23°C and 50 RH in accordance with JIS P8147 when the resin layers (A) of the obtained laminate are superposed on each other, and which is characterized in that the polyethylene resin composition (E) contains an ethylene-propylene copolymer (C) having the following characteristics (c-1) to (c-5), and a high-pressure radical polymerization low-density polyethylene (D) having the following characteristics (d-1) to (d-2). Ethylene-propylene copolymer (C): (c-1) Contains 75 to 93 mol% of structural units derived from ethylene as a major component, 7 to 25 mol% of structural units derived from propylene as an essential minor component, and may contain up to 7 mol% of structural units derived from a third α-olefin other than ethylene and propylene as a minor component. (However, when the structural units derived from the third α-olefin are contained, the total content of the structural units derived from ethylene, the structural units derived from propylene, and the structural units derived from the third α-olefin does not exceed 100 mol %). (c-2) MFR (190℃, 21.18N load) is 1-100g / 10min (c-3) Density is 0.87 to 0.91 g / cm3 (c-4) The total amount of vinyl and vinylidene in ethylene-propylene copolymer is 0.20 (pieces / total 1000C) or more (Note that the number of vinyl and vinylidene units is the number per 1,000 carbon atoms in the main chain and side chains, measured by NMR.) (c-5) The number of comonomer branches (Y) and density (X) in the ethylene-propylene copolymer satisfy the relationship shown in formula (1) below. Formula (1): (Y) ≧ -1360 × (X) + 1270 (where Y is the number per 1000 carbon atoms in total in the main chain and side chains as measured by NMR.) High pressure radical polymerization low density polyethylene (D); (d-1) MFR (190℃, 21.18N load) is 0.1 to 20g / min (d-2) Density is 0.915 to 0.930 g / cm 3 Effect of the Invention

[0014] The highly slippery film of the present invention has excellent slip properties between resin layers, and does not impair the inherent required properties such as heat sealability as a packaging molded product. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a schematic diagram showing a cross section of an example of the laminate of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a cross section of another example of the laminate of the present invention. [Diagram 3] Figure 3 shows the relationship between the density of ethylene-propylene copolymers or other ethylene-α-olefin copolymers and the static friction coefficient measured by the gradient method. [Explanation of symbols]

[0016] 1 Base material layer (B) 2. A resin layer different from the resin layer (A) 3 Resin layer (A) DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The present invention relates to a polyethylene resin composition for high lubricity films and a high lubricity film laminate, characterized by comprising a resin layer containing a polyethylene resin composition including a specific ethylene-propylene copolymer and preferably a specific high-pressure radical polymerization low-density polyethylene, and a base layer. Hereinafter, each component used in the present invention and the laminate using them will be described in detail.

[0018] 1. Polyethylene resin composition (E) The polyethylene resin composition of the present invention (hereinafter, also simply referred to as the resin composition) is characterized by containing an ethylene-propylene copolymer (C), and preferably further contains a high-pressure radical polymerization low-density polyethylene (D), and more preferably contains 95 to 10% by weight of the ethylene-propylene copolymer (C) and 5 to 90% by weight of the high-pressure radical polymerization low-density polyethylene (D). Furthermore, as a third component, it may contain an ethylene-α-olefin copolymer (F) other than the ethylene-propylene copolymer (C) (however, when the third component ethylene-α-olefin copolymer is contained, the total of the third component ethylene-α-olefin copolymer (F), the ethylene-propylene copolymer (C) and the high-pressure radical polymerization low-density polyethylene (D) does not exceed 100% by weight).

[0019] (1) Ethylene-propylene copolymer (C) The ethylene-propylene copolymer (C) used in the present invention has the following characteristics (c-1) to (c-5): (c-1) Contains 75 to 93 mol% of structural units derived from ethylene as a major component, 7 to 25 mol% of structural units derived from propylene as an essential minor component, and may contain up to 7 mol% of structural units derived from a third α-olefin other than ethylene and propylene as a minor component. (However, when the above-mentioned structural units derived from the third α-olefin are contained, the total of the structural units derived from ethylene, the structural units derived from propylene, and the structural units derived from the third α-olefin does not exceed 100 mol %). (c-2) MFR (190℃, 21.18N load) is 1-100g / 10min (c-3) Density is 0.88 to 0.91 g / cm 3 (c-4) The total amount of vinyl and vinylidene in ethylene-propylene copolymer is 0.20 (pieces / total 1000C) or more (Note that the number of vinyl and vinylidene units is the number per 1,000 carbon atoms in the main chain and side chains, measured by NMR.) (c-5) The number of comonomer branches (Y) and density (X) in the ethylene-propylene copolymer satisfy the relationship shown in formula (1) below. Formula (1): (Y) ≧ -1360 × (X) + 1270 (where Y is the number per 1000 carbon atoms in total in the main chain and side chains as measured by NMR.)

[0020] In addition, copolymers consisting of ethylene and propylene include so-called ethylene propylene rubber (EPM), which contains more than 20 mol% propylene and has a density of 0.870 g / cm 3 Rubber-like polymers obtained by the following solution polymerization method are used in the field of elastomers, but the ethylene-propylene copolymer (C) of the present invention is a polymer that is completely different from these ethylene-propylene rubbers in terms of density range, amount of ethylene and propylene contained, and physical properties. In addition, propylene polymers, propylene-ethylene copolymers that contain a small amount of ethylene component during the manufacturing process are also known, but these are also significantly different from the ethylene-propylene copolymer (C) of the present invention in terms of propylene content, etc., and are polymers that are completely different in physical properties, etc. In addition, ethylene-α-olefin copolymers with so-called normal linear molecular structures (e.g., LLDPE) have been developed mainly for film applications, and therefore usually use C4 or higher α-olefins such as C4 (1-butene) and C6 (1-hexene) as the main comonomer components to obtain high-strength copolymers. There are also copolymers of ethylene and propylene that use C3 (propylene) comonomer as the main secondary component, which results in low strength, and have a density of 0.88 g / cm. 3 The above copolymers have so far attracted little attention, and at least have not been commercially available from the present applicant. Recently, the present inventors have newly produced ethylene-propylene copolymers using a C3 comonomer in this density range as the main secondary component, and conducted various studies, and have found that the effects of the present invention can be obtained in laminates containing polyethylene resin compositions using ethylene-propylene copolymers having physical properties in the new ranges, particularly (c-1) to (c-5).

[0021] (i) Properties of ethylene-propylene copolymer (C) (c-1) Monomer structure The ethylene-propylene copolymer (C) used in the present invention is an ethylene-propylene copolymer characterized by containing 75-93 mol% of structural units derived from ethylene as a main component and 7-25 mol% of structural units derived from propylene as a secondary component, and specifically, a copolymer obtained by polymerization by catalytic polymerization method, which is a copolymer obtained by substantially linear random polymerization. A specific example is a random copolymer of ethylene and propylene. Preferably, the structural units derived from ethylene are 82-92 mol% and the structural units derived from propylene are 8-25 mol%, more preferably, the structural units derived from ethylene are 75-90 mol% and the structural units derived from propylene are 10-25 mol%. Here, the monomer amount such as the ethylene content is 13 The values ​​were measured and calculated by C-NMR under the conditions described in the Examples below.

[0022] In addition, it is preferable that the copolymer does not contain any other α-olefins, particularly α-olefins having 4 to 20 carbon atoms, or other monomer components, but may contain such components in a substantially small amount. In this specification, an α-olefin other than ethylene and propylene is referred to as a third α-olefin. The ethylene-propylene copolymer (C) of the present invention may contain, as a minor component, a structural unit derived from a third α-olefin other than ethylene and propylene, for example, in an amount of 7 mol% or less, preferably 7 mol% or less, more preferably 5 mol% or less, even more preferably 1 mol% or less, and most preferably 0.5 mol% or less. Here, when the ethylene-propylene copolymer (C) of the present invention contains a structural unit derived from a third α-olefin, the total amount of the structural units derived from ethylene, the structural units derived from propylene, and the structural units derived from the third α-olefin does not exceed 100 mol%. In this case, the content of the structural units derived from propylene is preferably higher than the content of the structural units derived from the third α-olefin. When the ethylene-propylene copolymer (C) of the present invention contains a structural unit derived from a third α-olefin, one or more kinds of the third α-olefin can be used. The ethylene-propylene copolymer (C) may be one type or a combination of two or more types as long as it satisfies (c-1) to (c-5).

[0023] When propylene is used as a secondary component and is an essential comonomer, and in particular when high-pressure ionic polymerization using a metallocene catalyst (described later) is used, it is possible to obtain ethylene-α-olefin copolymers with a specifically high total number of vinyl and vinylidene units. This effect is difficult to obtain when α-olefins such as 1-butene, 1-hexene, and 1-octene are polymerized as the main comonomer.

[0024] (c-2)MFR The ethylene-propylene copolymer (C) used in the present invention has a melt flow rate (MFR: 190°C, 21.18N load) of 1 to 100g / 10min, preferably 1 to 80g / 10min, and more preferably more than 5g / 10min and 60g / 10min or less. If the MFR is less than 1g / 10min, the extensibility during lamination molding becomes poor and the motor load in the extruder becomes high, which is not preferable. On the other hand, if the MFR exceeds 100g / 10min, the state of the molten film during molding becomes unstable, which is not preferable. To adjust the MFR of a polymer, for example, the polymerization temperature, the amount of comonomer, etc. are appropriately adjusted. The MFR of ethylene-propylene copolymer is measured in accordance with JIS-K6922-2:1997 Appendix (190℃, 21.18N load).

[0025] (c-3) Density The ethylene-propylene copolymer (C) used in the present invention has a density of 0.87 to 0.91 g / cm 3 and preferably 0.87 to 0.90 g / cm 3 and more preferably 0.87 to 0.89 g / cm 3 The density is 0.87g / cm 3 If the density is less than 0.91 g / cm3, blocking will be poor, which is not preferable. 3 If it exceeds this value, the slipperiness becomes poor, which is not preferable. The density of the polymer can be adjusted by, for example, adjusting the comonomer content, polymerization temperature, catalyst amount, etc. The density of ethylene-propylene copolymer is measured in accordance with JIS-K6922-2:1997 Appendix (for low-density polyethylene) (measurement temperature 23°C).

[0026] (c-4) Total number of vinyls and vinylidenes In copolymers obtained by copolymerizing ethylene with one or more α-olefins, even if diene monomers are not actively added, various double bonds (vinyl, vinylidene, cis-vinylene, trans-vinylene, tri-substituted olefins) may be produced due to differences in the mechanisms of the production process, and the amounts and types of double bonds vary. It was previously known that in order to obtain good cross-linking properties for use as a solar cell encapsulant, the more double bonds contained in an ethylene-α-olefin copolymer, the better the cross-linking properties. However, in the field of resin compositions for high-slip films, the differences in the amount and type of double bonds had not been investigated. In the present invention, it has been discovered that, among the various double bonds contained in an ethylene-propylene copolymer, vinyl and vinylidene are particularly important in terms of lubricity, and it has been found that the effects of the present invention can be achieved by producing an ethylene-propylene copolymer in which the total number of vinyl and vinylidene is greater than that of a normal ethylene-α-olefin copolymer and using the copolymer as an ethylene-propylene copolymer for a lamination resin composition, and thus the present invention has been completed.

[0027] The ethylene-propylene copolymer (C) used in the present invention has a total number of vinyl and vinylidene double bonds per 1000 carbon atoms in the main chain and side chains measured by NMR of 0.20 (units / total 1000C) or more, preferably 0.30 to 5.0 (units / total 1000C), more preferably 0.35 to 4.5 (units / total 1000C), and even more preferably 0.50 to 4.0 (units / total 1000C). When the total number of vinyl and vinylidene is within the above range, the resin composition has excellent slipperiness, and when it is less than 0.20, the slipperiness is insufficient. The total number of vinyl and vinylidene can be controlled within the above range by appropriately selecting a suitable metallocene catalyst, adjusting the polymerization temperature, the type of comonomer, and the amount of comonomer. The number of double bonds is the number per 1,000 carbon atoms in the main chain and side chains in total, and is a value calculated using the integrated intensity of characteristic peaks in 1H-NMR spectrum, measured and calculated under the conditions described in the Examples below.

[0028] Furthermore, in the present invention, the number of vinyl groups in the ethylene-propylene copolymer (C) preferably satisfies the range of 0.1 (groups / total 1000C) or more. In the present invention, the number of vinylidenes in the ethylene-propylene copolymer (C) preferably satisfies the range of 0.05 (units / total 1000C) or more.

[0029] (c-5) Relationship between branch number (Y) and density (X) due to comonomer The ethylene-propylene copolymer (C) used in the present invention preferably has a branch number (Y) and density (X) due to comonomers that satisfy the following formula (1). When the density and the number of branches satisfy the relationship of the above formula (1), the number of branches due to the comonomer is sufficiently ensured, resulting in a resin composition with excellent slip properties. Here, the number of branches due to comonomers (Y) is the number per 1000 total carbon atoms in the main chain and side chains (units / total 1000C) measured by NMR for ethylene-propylene copolymer (C). Furthermore, density (X) is the density of the ethylene-propylene copolymer (C) and is measured as described above.

[0030] The number of branches (Y) due to comonomers indicates the amount of tertiary carbons contained in the polymer, and is the number per 1000 carbon atoms in total in the main chain and side chains measured by NMR. For example, it can be calculated from 13C-NMR spectrum with reference to EW Hansen, R. Blom, and OM Bade, Polymer, Vol. 36, p. 4295 (1997). The relationship between the density and the number of branches can be adjusted by the polymerization conditions such as the type and ratio of the comonomers to be copolymerized and the polymerization temperature.

[0031] (ii) Polymerization catalyst and polymerization method for ethylene-propylene copolymer (C) The catalyst used in the production of the ethylene-propylene copolymer (C) used in the present invention is not particularly limited, but a metallocene catalyst is more preferably used. The metallocene catalyst is not particularly limited, but may be a catalyst containing a metallocene compound such as a zirconium compound coordinated with a group having a cyclopentadienyl skeleton and a cocatalyst as a catalytic component. In particular, it is preferable to use a metallocene compound such as a zirconium compound coordinated with a group having a cyclopentadienyl skeleton. The production method is not particularly limited, and a high-pressure ionic polymerization method, a gas phase method, a solution method, a slurry method, etc. can be used. However, in order to obtain the ethylene-propylene copolymer (C) according to the present invention having adjusted double bonds, it is desirable to carry out the polymerization at a high temperature of 150 to 330°C, and therefore it is preferable to use a high-pressure ionic polymerization method ("Polyethylene Technology Reader", Chapter 4, edited by Kazuo Matsuura and Naotaka Mikami, 2001).

[0032] (2) Low-density polyethylene produced by high-pressure radical polymerization (D) The high-pressure radical polymerization low-density polyethylene (D) used in the present invention (hereinafter also simply referred to as low-density polyethylene (D)) is a low-density polyethylene (LDPE) obtained by a high-pressure radical polymerization method and having the following characteristics (d-1) to (d-2), and is preferably a long-chain branched low-density polyethylene. (d-1) MFR (190℃, 21.18N load) is 0.1 to 20g / 10min (d-2) Density is 0.915 to 0.930 g / cm 3

[0033] (i) Characteristics of low-density polyethylene produced by high-pressure radical polymerization (D) (d-1)MFR The melt flow rate (MFR: 190°C, 21.18N load) of the low-density polyethylene (D) used in the present invention is 0.1 to 20g / 10min, preferably 0.5 to 15g / 10min, more preferably 1 to 15g / 10min. If the MFR is less than 0.1g / 10min, the extensibility is insufficient and film breakage occurs during high-speed molding. On the other hand, if the MFR exceeds 20g / 10min, the molten film becomes unstable. Here, MFR is a value measured in accordance with JIS-K6922-2:1997 Appendix (190°C, 21.18N load).

[0034] (d-2) Density The density of the low-density polyethylene (D) used in the present invention is 0.915 to 0.930 g / cm3, preferably 0.916 to 0.926 g / cm3, and more preferably 0.917 to 0.925 g / cm3. If the density is less than 0.915 g / cm3, the stickiness increases. On the other hand, if the density exceeds 0.93 g / cm3, the adhesiveness becomes poor. Here, the density is measured in accordance with JIS-K6922-2:1997 Appendix (for low density polyethylene) (measurement temperature: 23° C.).

[0035] (ii) High-pressure radical polymerization method for polymerizing low-density polyethylene (D) The low-density polyethylene (D) used in the present invention is generally produced by polymerizing ethylene in a tank reactor or tubular reactor in the presence of a radical generator under conditions of a polymerization pressure of 1000 to 3000 kg / cm2 and a polymerization temperature of 150 to 300° C. The MFR can be adjusted by using hydrogen or a hydrocarbon such as methane or ethane as a molecular weight regulator.

[0036] (3) Composition ratio of ethylene-propylene copolymer (C) and low-density polyethylene (D) In the case where the polyethylene resin composition (E) used in the present invention contains an ethylene-propylene copolymer (C) and a low-density polyethylene (D), the ratio of the ethylene-propylene copolymer (C) to the high-pressure radical polymerization low-density polyethylene (D) is, for example, 5-95% by weight: 5-95% by weight, preferably 10-95% by weight: 5-90% by weight, more preferably 15-95% by weight: 5-75% by weight. More preferably, it is 20-95% by weight: 5-80% by weight. If the amount of the ethylene-propylene copolymer (C) is too large, the stability of the molten film may decrease, and if the amount of the high-pressure radical polymerization low-density polyethylene (D) is too large, the slipperiness may deteriorate. Furthermore, an ethylene-α-olefin copolymer may be added as a third component.

[0037] (4) Characteristics of polyethylene resin composition (E) (e-1)MFR The melt flow rate (MFR: 190°C, 21.18N load) of the polyethylene resin composition (E) used in the present invention is preferably 1 to 100g / 10min, more preferably 1 to 80g / 10min, and even more preferably 5 to 60g / 10min. If the MFR is less than 1g / 10min, the extensibility during molding is deteriorated and the motor load in the extruder is increased, which is not preferable. On the other hand, if the MFR exceeds 100g / 10min, the state of the molten film during molding becomes unstable, which is not preferable. Here, MFR is a value measured in accordance with JIS-K6922-2:1997 Appendix (190°C, 21.18N load).

[0038] (e-2) Density The density of the polyethylene resin composition (E) used in the present invention is preferably 0.88 to 0.94 g / cm 3 and more preferably 0.88 to 0.93 g / cm 3 and more preferably 0.88 to 0.92 g / cm 3 The density is 0.88g / cm 3 If the density is less than 0.94 g / cm3, blocking will be poor, which is not preferable. 3 If it exceeds this value, the slipperiness becomes poor, which is not preferable. Here, the density is measured in accordance with JIS-K6922-2:1997 Appendix (for low density polyethylene) (measurement temperature: 23° C.).

[0039] (5) Other ingredients The polyethylene resin composition (E) used in the present invention or the resin layer (A) containing it may contain additives such as phenolic or phosphorus-based antioxidants, stabilizers such as metal soaps, antiblocking agents, lubricants, dispersants, pigments such as organic or inorganic colorants, antifogging agents such as unsaturated fatty acid esters, antistatic agents, ultraviolet absorbers, light stabilizers, nucleating agents, etc., which are commonly used in polyethylene resins, as necessary, so long as they do not impair other packaging qualities such as slipperiness and heat seal strength. For example, the preferred range of antioxidants is 5000 ppm or less, more preferably 3000 ppm or less, and even more preferably 1000 ppm or less, by weight. Furthermore, other thermoplastic resins, such as polyethylene-based resins such as LDPE, C4-LLDPE, HAO-LLDPE, ethylene-vinyl acetate copolymer (EVA), ethylene-acrylic acid copolymer (EAA), ethylene-methacrylic acid copolymer (EMAA), ethylene-acrylic acid ester copolymer (EEA, EMA, EMMA, etc.), and high-density polyethylene (HDPE), adhesive resins such as ethylene-maleic anhydride copolymer, polypropylene-based resins, and polystyrene resins, may be blended therein, so long as the properties of the polyethylene resin composition layer are not impaired. Moreover, it is preferable that the polyethylene resin composition (E) of the present invention does not contain a crosslinking agent.

[0040] 2. Base material layer (B) The substrate layer (B) used in the present invention may be, for example, a monolayer film of nylon, polyester, polypropylene, polyethylene, ethylene-vinyl alcohol copolymer, or the like, or a laminate film made of the same or different materials. The film is preferably a stretched film. In addition, examples of the substrate layer (B) include monolayer substrates such as paper such as kraft paper, metal foil such as aluminum or copper, plastic films vapor-deposited with metals, inorganic substances, or organic substances, or laminate substrates such as plastic films vapor-deposited with a barrier coating. The substrate layer may be printed or coated with various coatings. The substrate layer may be partially or entirely printed with colored inks by a conventional method. The ink may be appropriately selected from conventionally known inks.

[0041] 3.Laminate The laminate of the present invention has at least two layers, a resin layer (A) containing the above-mentioned polyethylene resin composition (E) and a substrate layer (B), and the resin layer (A) is formed by adhering directly onto the substrate layer (B) or onto another resin layer laminated onto the substrate layer. On at least one surface of the substrate layer (B), a resin layer (A) containing the polyethylene resin composition (E) is formed by adhering directly onto the substrate layer or onto another resin layer laminated onto the substrate layer. There are no restrictions on the structure of the laminate, but examples of the laminate include those having the following structures: Base layer (B) / resin layer (A) containing resin composition (E), base layer (B) / other resin layer / resin layer (A) containing resin composition (E), resin layer (A) containing resin composition (E) / base layer (B) / resin layer (A) containing resin composition (E), resin layer (A) containing resin composition (E) / other resin layer / base layer (B) / resin layer (A) containing resin composition (E), resin layer (A) containing resin composition (E) / other resin layer / base layer (B) / resin layer (A) containing resin composition (E), resin layer (A) containing resin composition (E) / other resin layer / base layer (B) / other resin layer / resin layer (A) containing resin composition (E), base layer (B) / resin layer (A) containing resin composition (E) / base layer (B) , base layer (B) / other resin layer / resin layer (A) containing resin composition (E) / base layer (B), resin layer (A) containing resin composition (E) / base layer (B) / resin layer (A) containing resin composition (E) / base layer (B) / resin layer (A) containing resin composition (E) / base layer (B) / resin layer (A) containing resin composition (E) / base layer (B), resin layer (A) containing resin composition (E) / other resin layer / base layer (B) / resin layer (A) containing resin composition (E) / base layer (B) / resin layer (A) containing resin composition (E) / base layer (B), resin layer (A) containing resin composition (E) / other resin layer / base layer (B) / resin layer (A) containing resin composition (E) / base layer (B), resin layer (A) containing resin composition (E) / other resin layer / base layer (B) ) / other resin layer / resin layer (A) containing resin composition (E) / substrate layer (B) / resin layer (A) containing resin composition (E) / substrate layer (B), resin layer (A) containing resin composition (E) / other resin layer / substrate layer (B) / other resin layer / resin layer (A) containing resin composition (E) / other resin layer / substrate layer (B) / resin layer (A) containing resin composition (E) / other resin layer / substrate layer (B) / resin layer (A) containing resin composition (E) / substrate layer (B), resin layer (A) containing resin composition (E) / other resin layer / substrate layer (B) / other resin layer / resin layer (A) containing resin composition (E) / other resin layer / substrate layer (B) / other resin layer / resin layer containing resin composition (E) layer (A) / substrate layer (B), resin layer (A) containing resin composition (E) / other resin layer / substrate layer (B) / other resin layer / resin layer (A) containing resin composition (E) / other resin layer / substrate layer (B) / other resin layer / resin layer (A) containing resin composition (E) / other resin layer / substrate layer (B), substrate layer (B) / resin layer (A) containing resin composition (E) / other resin layer, other resin layer / substrate layer (B) / resin layer (A) containing resin composition (E), other substrate layer / substrate layer (B) / resin layer (A) containing resin composition (E), substrate layer (B) / resin layer (A) containing resin composition (E) / other resin layer A particularly preferred embodiment of the present invention is a high-slip film laminate, wherein the resin layer (A) is an outermost layer or an innermost layer of the laminate. Here, the other substrate layer is a substrate layer different from the substrate layer (B), and examples thereof include plastic films or sheets such as polyamide resins, polyester resins, saponified ethylene-vinyl acetate copolymers, polyvinylidene chloride, polycarbonate, etc., stretched products of the above-mentioned films or sheets, printed materials, secondary processed films or sheets such as vapor deposition products of metals, metal foils or metal plates such as aluminum, iron, copper, and alloys containing these as main components, cellophane, paper, woven fabric, nonwoven fabric, etc. The other resin layer is a resin layer different from the resin layer (A), and examples thereof include polyethylene resins such as LDPE, C4-LLDPE, HAO-LLDPE, ethylene-vinyl acetate copolymer (EVA), ethylene-acrylic acid copolymer (EAA), ethylene-methacrylic acid copolymer (EMAA), ethylene-acrylic acid ester copolymer (EEA, EMA, EMMA, etc.), high density polyethylene (HDPE), and other thermoplastic resins, adhesive resins such as ethylene-maleic anhydride copolymer, polypropylene resins, polystyrene resins, and the like.

[0042] The method for producing the laminate is not particularly limited, but for example, the so-called extrusion coating method in which a polyethylene resin composition is melt-extruded and laminated on a substrate layer is preferred. The extrusion coating is preferably performed by laminating one or more layers by a method such as single layer, sandwich lamination, coextrusion lamination, or tandem lamination. The resin layer (A) containing the polyethylene resin composition (E) can be used as an adhesive layer and also as a sealant for the surface layer.

[0043] In addition, the method for ensuring adhesion to the paper substrate layer is not particularly limited, but for example, the substrate may be surface-treated. Examples of the surface treatment method include various treatment methods such as corona discharge treatment, ozone treatment, frame treatment, and low-temperature plasma treatment. Another example is a method of spraying ozone onto molten resin. In addition, when a substrate layer other than the paper substrate is provided, it is preferable to perform anchor coating treatment as necessary.

[0044] The laminate of the present invention is formed from a resin layer (A) containing the above-mentioned polyethylene resin composition (E), and is a laminate having excellent slip properties.

[0045] The polyethylene resin composition and laminate of the present invention exhibit excellent sliding properties between inner surfaces without impairing qualities such as heat seal strength, etc. Therefore, they can be used as highly slippery films in various fields, such as retort pouches that require easy sliding properties and food packaging materials for confectionery, bread, etc. that require easy opening of bags.

[0046] The high slip film of the present invention means a film having high slip on the surface of the film, that is, the surface of the outermost layer or the surface of the innermost layer. The standard of high slip is that the resin layers (A) of the obtained laminate are stacked together, and the static friction coefficient measured by the inclination method under the conditions of 23°C-50RH in accordance with JIS P8147 is less than 0.5. The smaller the static friction coefficient, the better the slip property. Considering bag making, printing, product filling, and the like, the static friction coefficient is desirably less than 0.5, preferably 0.45 or less, more preferably 0.35 or less, and even more preferably 0.3 or less. In particular, the high-slip film of the present invention is preferably composed of a resin composition that does not contain any lubricant that is a low molecular weight compound, or contains only a reduced amount of such a lubricant. Even in such an embodiment, one of the features is that the film has high slipperiness. EXAMPLES

[0047] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. The measurement methods and resins used in the examples and comparative examples are as follows.

[0048] 1.Measurement method (1) Melt flow rate (MFR): The MFR of ethylene-propylene copolymer or other ethylene-α-olefin copolymer, high-pressure radical polymerization low-density polyethylene, and polyethylene resin composition was measured in accordance with JIS-K6922-2:1997 Appendix (190℃, 21.18N load). (2) Density: The density of ethylene-propylene copolymer or other ethylene-α-olefin copolymer, high-pressure radical polymerization low-density polyethylene, and polyethylene resin composition was measured in accordance with JIS-K6922-2:1997 Appendix (23°C, in the case of low-density polyethylene).

[0049] (3) Monomer amount, number of branches, number of double bonds: <Sample preparation and measurement conditions> 200 mg of the sample was dissolved in an NMR sample tube with an inner diameter of 10 mm together with 2.4 ml of o-dichlorobenzene / deuterated bromide benzene = 4 / 1 (volume ratio) and hexamethyldisiloxane as a chemical shift standard substance. NMR measurements were performed using a Bruker Biospin AV400M NMR instrument equipped with a 10 mm diameter cryoprobe. 13 The C-NMR measurement conditions were a sample temperature of 120°C, a pulse angle of 90°, a pulse interval of 20 seconds, and an accumulation number of 128. The measurement was performed using the broadband decoupling method. 1 The H-NMR measurement conditions were a sample temperature of 120° C., a pulse angle of 4.5°, a pulse interval of 2 seconds, and an accumulation number of 512. <Calculation method> (i) Monomer amount and number of branches due to comonomers 13 Using the signal intensity of the C-NMR spectrum, propylene, The amounts of hexene and ethylene were determined. C3(mol%)=I(P)×100 / [I(P)+I(H)+I(E)] C6(mol%)=I(H)×100 / [I(P)+I(H)+I(E)] C2(mol%)=I(E)×100 / [I(P)+I(H)+I(E)] Here, I(P), I(H), and I(H) are quantities expressed by the following formulas, respectively. I(P) = 0.5 × (I 37.69~37.20 +I 37.90~37.69 +I 37.97~37.90 +I 43.90~42.68 )+I 46.60~45.39 I(H) = 0.5 × (I 34.56~34.22 +I 34.94~34.86 +I 43.60~42.68 ) + 0.5 × (I 34.86~34.70 -I 35.80~35.68 )+I 40.10~39.96 +I 40.80~40.70 I(E)={0.5×(I 34.94~34.86 +I 37.90~37.69 I 37.97~37.90 +I 34.56~34.22 +I 37.69~37.20 ) + 0.5 × (I 34.86~34.70 -I 35.80~35.68 )+I 24.90~24.70 +I 24.70~24.52 +I 24.52~24.32 +I 27.28~26.83 +I 27.50~27.28 +I 31.50~28.50 -I(H)} / 2 I is the integrated intensity, and the subscripts of I indicate the range of chemical shifts. For example, I 37.69~37.20 indicates the integrated intensity of the 13C signal detected between 37.69 ppm and 37.20 ppm. The chemical shift was set to 1.98 ppm for the 13C signal of hexamethyldisiloxane, and the chemical shifts of other 13C signals were based on this. The number of branches per 1,000 carbon atoms in total in the main chain and side chains was calculated by the following formula. Number of methyl branches (units / total 1000C) =C3(mol%)×1000 / {C3(mol%)×3+C6(mol%)×6+ C2(mol%)×2} Number of butyl branches (pcs / total 1000C) =C6(mol%)×1000 / {C3(mol%)×3+C6(mol%)×6+ C2(mol%)×2}

[0050] (ii) Number of double bonds The total number of unsaturated bonds per 1,000 carbon atoms in the main chain and side chains is 1 The signal intensity of the H-NMR spectrum was used to calculate the value according to the following formula: Number of vinylidene units (units / total 1000C) = Ivd x 1000 / Itotal Number of vinyl pieces (pieces / total 1000C) = Ivi x 1000 / Itotal Number of trisubstituted olefins (units / total 1000C) = Itri × 1000 / Itotal Number of vinylenes (pieces / total 1000C) = Ivnl x 1000 / Itotal I is the integrated intensity, and the subscripts on I indicate the range of chemical shifts. Here, Ivd 、 Ivi, Itri, Ivnl, and Itotal are expressed by the following formulas. This is the amount. Ivd=(I 4.88~4.44 ) / 2 Ivni=(I 5.52~5.30 ) / 2 Ivi=(I 5.05~4.88 +I 5.85~5.70 ) / 3 Itri=I 5.30~5.05 Itotal = (I 0.00~5.85 ) / 2 However, for example, I 5.52~5.30 indicates the integrated intensity of the proton signal detected between 5.52 ppm and 5.30 ppm. The chemical shifts were set to 0.09 ppm based on the proton signal of hexamethyldisiloxane, and the chemical shifts of the signals due to other protons were based on this.

[0051] (4) Static friction coefficient (tan θ): Examples 1 to 5 and Comparative Examples 1 to 5 In a laminating machine, Toyobo Co., Ltd.'s polyethylene terephthalate film T4102 (thickness: 12 μm) was unwound from the unwinding machine to form the substrate, and a mixture of Toyo-Morton Co., Ltd.'s Olivine EL420 and methanol in a 1:6 ratio was applied to the substrate surface as an anchor coating agent, and extrusion lamination processing was carried out under the conditions described below. Extruder: 90mmΦ, L / D=28 Screw compression ratio: 4.0 Die: Lip opening: 0.7mm, Lip land: 3mm Air gap: 115mm Cooling roll temperature: 20℃ Lip resin temperature: 320℃ Take-off speed: 100m / min Base material width: 500mm Sample thickness: 20 μm The two obtained laminates were placed in an atmosphere of 23°C and 50% RH, and the static friction coefficient was measured by the inclination method with the resin layers (A) facing each other in accordance with JIS P8147. The smaller the static friction coefficient value, the better the slipperiness. Considering bag making, printing, product filling, and the like, the static friction coefficient is desirably less than 0.5, and more desirably 0.3 or less.

[0052] (5) Heat seal strength The two laminates obtained above were heat-sealed together at the resin layers (A) at a sealing temperature of 110°C or 150°C under an atmosphere of 23°C and 50% RH for 1 second at 0.2 MPa, and the heat seal strength of a 15 mm width was measured in accordance with JIS Z1713.

[0053] 2.Resin materials (1) Ethylene-propylene copolymer (A) or other ethylene-α-olefin copolymer, ethylene-α-olefin copolymer (B) were prepared by the following manufacturing method. (PE-1) to (PE-7) were used as component (C) ethylene-propylene copolymer or other ethylene-α-olefin copolymer, and (PE-8) to (PE-11) were used as component (F). The physical properties are shown in Table 1.

[0054] Manufacturing methods of (PE-1) to (PE-11) (i) Preparation of the catalyst A catalyst solution was prepared by adding an equimolar amount of “N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate” to 0.05 moles of the complex “rac-dimethylsilylenebisindenylhafnium dimethyl” prepared by the method described in JP-A-10-218921, and diluting the mixture to 50 L with toluene.

[0055] (ii) Polymerization method A 5.0-liter stirred autoclave continuous reactor was used, and the pressure inside the reactor was kept at 80 MPa. The feed gas was continuously supplied at a rate of 40 kg / hour while appropriately adjusting the amounts of ethylene, propylene, and 1-hexene. The catalyst solution described in the above section "(i) Preparation of catalyst" was continuously supplied, and the polymerization temperature was appropriately adjusted within the range of 150 to 250°C to obtain an ethylene-α-olefin copolymer. The physical properties of the obtained ethylene-propylene copolymer (C) or other ethylene-α-olefin copolymer, ethylene-α-olefin copolymer (F) are shown in Table 1.

[0056] (2) Low-density polyethylene produced by high-pressure radical polymerization The low-density polyethylenes (PE-12) to (PE-13) prepared by high-pressure radical polymerization and having the physical properties shown in Table 1 were used.

[0057] Example 1 The ethylene-propylene copolymer (C) was 40% by weight of (PE-1), the ethylene-α-olefin copolymer (F) was 40% by weight of (PE-8), which is a copolymer of ethylene and 1-hexene, and the high-pressure low-density polyethylene (D) had an MFR of 4 g / 10 min and a density of 0.918 g / cm. 3 A polyethylene resin composition (E) consisting of 20% by weight of the long-chain branched low-density polyethylene (PE-12) prepared by high-pressure radical polymerization was granulated in a 40 mm single-screw extruder to obtain pellets of the polyethylene composition. In order to evaluate the above-mentioned (4) static friction coefficient and (5) heat seal strength using the pellets obtained above, a polyethylene terephthalate film T4102 (thickness: 12 μm) made by Toyobo Co., Ltd. was fed from a feeder in a laminating machine to be used as a substrate, and a mixture of Olivine EL420 and methanol made by Toyo-Morton Co., Ltd. in a ratio of 1:6 was applied to the substrate surface as an anchor coat agent, and extrusion lamination was performed under the conditions described below to obtain a laminate of a resin layer (A) containing a polyethylene resin composition (E), and each evaluation was performed. The evaluation results of the laminate are shown in Table 1. Extruder: 90mmΦ, L / D=28 Screw compression ratio: 4.0 Die: Lip opening: 0.7mm, Lip land: 3mm Air gap: 115mm Cooling roll temperature: 20℃ Lip resin temperature: 320℃ Take-off speed: 100m / min Base material width: 500mm Sample thickness: 20 μm

[0058] Example 2 Pellets and a laminate were prepared and evaluated in the same manner as in Example 1, except that 40% by weight of (PE-2) was used instead of (PE-1) as the ethylene-propylene copolymer (C) and 40% by weight of (PE-9) was used as the ethylene-α-olefin copolymer (F), which is a copolymer of ethylene and 1-hexene. The evaluation results are shown in Table 1.

[0059] Example 3 Pellets and laminates were prepared and evaluated in the same manner as in Example 1, except that 34% by weight of (PE-3) was used instead of (PE-1) as the ethylene-propylene copolymer (C) and 46% by weight of (PE-10) was used as the ethylene-α-olefin copolymer (F), which is a copolymer of ethylene and 1-hexene. The evaluation results are shown in Table 1.

[0060] Example 4 Pellets and laminates were prepared and evaluated in the same manner as in Example 1, except that 31% by weight of (PE-4) was used instead of (PE-1) as the ethylene-propylene copolymer (C) and 49% by weight of (PE-8) was used as the ethylene-α-olefin copolymer (F), which is a copolymer of ethylene and 1-hexene. The evaluation results are shown in Table 1.

[0061] Example 5 Pellets and a laminate were prepared and evaluated in the same manner as in Example 1, except that 20% by weight of (PE-4) was used as the ethylene-propylene copolymer (C) instead of (PE-1) and 80% by weight of high-pressure radical polymerization method long-chain branched low-density polyethylene (PE-13) having MFR of 7 g / 10 min and density of 0.918 g / cm3 was used as the high-pressure low-density polyethylene (D). The evaluation results are shown in Table 1.

[0062] Comparative Example 1 Pellets and laminates were prepared and evaluated in the same manner as in Example 1, except that 40% by weight of ethylene-α-olefin copolymer (PE-5), a copolymer of ethylene, propylene, and 1-hexene, was used instead of ethylene-propylene copolymer (PE-1), and 40% by weight of (PE-8) was used as ethylene-α-olefin copolymer (F), a copolymer of ethylene and 1-hexene. The evaluation results are shown in Table 1.

[0063] Comparative Example 2 Pellets and laminates were prepared and evaluated in the same manner as in Example 1, except that 45% by weight of ethylene-α-olefin copolymer (PE-6), a copolymer of ethylene, propylene, and 1-hexene, was used instead of ethylene-propylene copolymer (PE-1), and 35% by weight of (PE-11) was used as ethylene-α-olefin copolymer (F), a copolymer of ethylene and 1-hexene. The evaluation results are shown in Table 1.

[0064] Comparative Example 3 Pellets and a laminate were prepared and evaluated in the same manner as in Example 1, except that 80% by weight of (PE-7) was used as the ethylene-propylene copolymer (C) instead of (PE-1). The evaluation results are shown in Table 1.

[0065] Comparative Example 4 Pellets were prepared and evaluated in the same manner as in Example 1, except that the ethylene-propylene copolymer (C) was not used, and a composition obtained only from the high-pressure radical polymerization low-density polyethylene (D) (PE-13) was used. The evaluation results are shown in Table 1.

[0066] Comparative Example 5 Pellets and a laminate were prepared and evaluated in the same manner as in Example 1, except that the ethylene-propylene copolymer (C) was not used, and 0.081% by weight of erucamide and 0.069% by weight of ethylene bis oleamide were added as lubricants to (PE-13), which is a low-density polyethylene (D) prepared by high-pressure radical polymerization. The evaluation results are shown in Table 1.

[0067] [Table 1]

[0068] The relationship between the density of the ethylene-propylene copolymers (C) or other ethylene-α-olefin copolymers of Examples 1 to 5 and Comparative Examples 1 to 5 obtained from Table 1 and the static friction coefficients measured by the gradient method in accordance with JIS P8147 is shown in a graph in FIG. 3. In the graph, the X-axis (horizontal axis) indicates the density of the ethylene-propylene copolymer or other ethylene-α-copolymer used in the study, and the Y-axis (vertical axis) indicates the static friction coefficient by the gradient method according to JIS P 8147. A smaller value on the Y-axis indicates better slipperiness, which is preferable. As is clear from the results in Table 1 and FIG. 3, the polyethylene resin compositions for high lubricity films according to the examples of the present invention and the high lubricity film laminates obtained therefrom had excellent lubricity commensurate with their density, and also had good low-temperature heat seal strength when heat sealed at 110°C and good high-temperature heat seal strength when heat sealed at 150°C. On the other hand, when the value calculated from a specific formula defined by the number of branches due to the comonomer and the density of the ethylene-α-olefin copolymer exceeds the number of branches of the comonomer (Comparative Examples 1 and 2), the slip property commensurate with the density becomes high and not good. In addition, the density of the ethylene-propylene copolymer (C) is 0.910 g / cm 3 When a material having a higher value was used (Comparative Example 3), the static friction coefficient was also high and the slipperiness was not good. In addition, even when the ethylene-propylene copolymer (C) was not used and only the high-pressure radical polymerization method low-density polyethylene (D) was used (Comparative Example 4), the static friction coefficient was high and the slipperiness was not good. In addition, when the ethylene-propylene copolymer (C) was not used, and only the high-pressure radical polymerization low-density polyethylene (D) was used with the addition of a lubricant (Comparative Example 5), the static friction coefficient was low and the slipperiness was good, but the high-temperature heat seal strength deteriorated when heat-sealed at 150°C. [Industrial Applicability]

[0069] The polyethylene resin composition of the present invention and a laminate comprising the same can be used as a highly lubricated film or the like which requires high lubricity.

Claims

1. A highly lubricating film laminate having at least two layers, namely a resin layer (A) and a base layer (B), wherein the resin layer (A) is formed directly on the base layer (B) or by laminating it on another resin layer laminated on the base layer (B), and wherein when the resin layers (A) of the obtained laminate are superimposed on each other, the static friction coefficient measured under the conditions of 23°C-50RH in accordance with JIS P8147 is less than 0.5 by an inclined method, and further wherein the resin layer (A) and the polyethylene resin composition (E) constituting the resin layer (A) satisfy the following properties: Resin layer (A): A polyethylene resin composition (E) containing an ethylene-propylene copolymer (C) having the following characteristics (c-1) to (c-5). (c-1) Contains 75 to 93 mol % of structural units derived from ethylene as a major component, 7 to 25 mol % of structural units derived from propylene as an essential minor component, and may contain 7 mol % or less of structural units derived from a third α-olefin other than ethylene and propylene as a minor component. (However, when the structural units derived from the third α-olefin are contained, the total amount of the structural units derived from ethylene, the structural units derived from propylene, and the structural units derived from the third α-olefin does not exceed 100 mol %). (c-2) MFR (190°C, 21.18N load) is 1 to 100g / 10min (c-3) density is 0.87 to 0.91 g / cm 3 (c-4) The total amount of vinyl and vinylidene in the ethylene-propylene copolymer is 0.20 (pieces / total 1000C) or more (Note that the number of vinyl and vinylidene groups is the number per 1,000 carbon atoms in total in the main chain and side chains as measured by NMR.) (c-5) The number of branches (Y) due to comonomers in the ethylene-propylene copolymer and the density (X) satisfy the relationship of the following formula (1). Formula (1): (Y)≧−1360×(X)+1270 (where Y is the number per 1000 total carbon atoms in the main chain and side chains as measured by NMR.) Polyethylene resin composition (E): Contains a high-pressure radical polymerization low-density polyethylene (D) having the following characteristics (d-1) to (d-2): (d-1) MFR (190°C, 21.18N load) is 0.1 to 20 g / min (d-2) Density is 0.915 to 0.930 g / cm 3

2. The highly lubricating film laminate according to claim 1, wherein the polyethylene resin composition (E) further satisfies the following properties (e-1) to (e-2). (e-1) MFR is 1 to 100 g / 10 min (e-2) density is 0.88 to 0.94 g / cm 3

3. 3. The high-slip film laminate according to claim 1, wherein the laminate is formed by an extrusion coating method.

4. 3. The high-smooth film laminate according to claim 1, wherein the resin layer (A) is an outermost layer or an innermost layer of the laminate.

5. A polyethylene resin composition (E) for use in a resin layer (A) used as an outermost layer or an innermost layer of a highly lubricating film laminate, wherein when the resin layers (A) of the resulting laminate are superposed on each other, the static friction coefficient by an inclination method measured under conditions of 23°C and 50RH in accordance with JIS P8147 is less than 0.5, and the polyethylene resin composition (E) contains an ethylene-propylene copolymer (C) having the following characteristics (c-1) to (c-5), and a low-density polyethylene (D) produced by a high-pressure radical polymerization method having the following characteristics (d-1) to (d-2). Ethylene-propylene copolymer (C): (c-1) Contains 75 to 93 mol % of structural units derived from ethylene as a major component, 7 to 25 mol % of structural units derived from propylene as an essential minor component, and may contain 7 mol % or less of structural units derived from a third α-olefin other than ethylene and propylene as a minor component. (However, when the structural units derived from the third α-olefin are contained, the total amount of the structural units derived from ethylene, the structural units derived from propylene, and the structural units derived from the third α-olefin does not exceed 100 mol %). (c-2) MFR (190°C, 21.18N load) is 1 to 100g / 10min (c-3) Density is 0.87 to 0.91 g / cm3 (c-4) The total amount of vinyl and vinylidene in the ethylene-propylene copolymer is 0.20 (pieces / total 1000C) or more (Note that the number of vinyl and vinylidene groups is the number per 1,000 carbon atoms in total in the main chain and side chains as measured by NMR.) (c-5) The number of branches (Y) due to comonomers in the ethylene-propylene copolymer and the density (X) satisfy the relationship of the following formula (1). Formula (1): (Y)≧−1360×(X)+1270 (where Y is the number per 1000 total carbon atoms in the main chain and side chains as measured by NMR.) High pressure radical polymerization low density polyethylene (D); (d-1) MFR (190°C, 21.18N load) is 0.1 to 20 g / min (d-2) Density is 0.915 to 0.930 g / cm 3

Citation Information

Patent Citations

  • Production of powderd rubber

    JP1982000147A

  • Lubricant for synthetic resin

    JP2003313432A

  • JP343353A